Measuring the vibrancy of urban neighborhoods using mobile phone data with an improved PageRank algorithm. Issue 2 (11th March 2019) - Jia, Chen; Du, Yunyan; Wang, Siying; Bai, Tianyang; Fei, Teng
Abstract: A neighborhood is a shared space for spatial interaction. The vibrancy of a neighborhood represents a synergy between the people, activities, and values in a place, which increases community vitality and spurs economic opportunity. It can be investigated both qualitatively and quantitatively. However, there are technical challenges involved in accurately charting vibrancy. With the recent advances in communication technology and the prevalence of location‐aware devices such as mobile phones, individual trajectories can be collected and analyzed on a large scale. In previous research, the weights of the vibrancies corresponding to different trajectories were not differentiated. In this study, an improved PageRank algorithm using a weighted bipartite graph is proposed to measure the vibrancy of an urban neighborhood from a different perspective, which highlights the differences between vibrancies arising from different types of citizens. This method connects the land much more closely with human activities and provides a new perspective on, and guidance for, urban resource allocation and urban planning.